Improving Student Learning Outcomes through the Use of the PQ4R Method Assisted by Powtoon Animation Video Media in Social Science Learning - Enjelin Thomas; Haspidawati Nur; Sunardin Sunardin (EDUJAVARE: International Journal of Educational Research, 2026)
Natural and Social Sciences (IPAS) is a course that is the result of the integration of Natural Sciences (IPA) and Social Sciences (IPS) which aims to help students understand the relationship between the natural and social environment in an integrated manner. This study aims to describe the improvement of learning outcomes of science students in grade IV of SDN 188 Barru, Barru Regency through the application of the PQ4R method assisted by Powtoon animation video media. This research is a Class Action (PTK) research conducted in Binuang Village, Balusu District, Barru Regency. The research subjects amounted to 9 students in grade IV. Data was collected through observation tests and learning outcomes using instruments in the form of observation sheets for learning implementation, observation sheets for student activities, and learning outcome tests. The results of the study showed an increase in learning implementation, student activities, and learning outcomes in each cycle. In Cycle I, the implementation of learning and student activities each reached 83% with the very good category, while the completeness of learning outcomes reached 33% with an average score of 56 (low category). After improvements were made in Cycle II, the implementation of learning and student activities increased to 97.3% with the very good category, while the completeness of learning outcomes increased to 77% with an average score of 74 (high category). Thus, the application of the PQ4R method fostered by Powtoon animation video media has been proven to improve the learning outcomes of fourth grade IPAS students of SDN 188 Barru, Barru Regency.